Improved Crop Varieties, Agronomic Practices, Soil Water Conservation Practices - International Maize and Wheat Improvement Center; International Institute of Tropical Agriculture; International Center for Tropical Agriculture; World Agroforestry Centre; Hombolo Agricultural Research Institute; Selian Agricultural Research Institute (International Food Policy Research Institute, 2016)
Establishment of demonstration plots on improved crop varieties (maize, groundnuts, soybeans and beans) and best-bet agronomic pratices and soil and water conservation practices in Babati, Kongwa, kiteto, Mvomero, Mbozi, Kilosa and Kilolo in Tanzania. Training of lead farmers and extension staff to empower them with knowledge on improved technologies so that they can also train others. This study contains data from different cereal legume rotation systems in northern Ghana. Project title: Enhancing Partnership among Africa RISING (AR), NAFAKA and TUBORESHE CHAKULA (TUBOCHA) Programs for Fast-Tracking Delivery and Scaling of Agricultural Technologies in Tanzania. Project abstract: This project is implemented in partnership between Africa RISING research team and NAFAKA and focuses on scaling of agricultural technologies that include deployment of improved maize varieties and legumes (beans, soybean, groundnuts), deployment of improved water and soil conservation practices and improved good agricultural practices in Babati, Kongwa, Kiteto, Kilosa, Mvomero, Mbozi and Kilolo districts of Tanzania. The project is implemented by CIMMYT, IITA, CIAT, ICRAF, ARI-Hombolo, AMINATA Quality Seeds compnay, Meru Agro-Tours and Cosultants seed company, NAFAKA and Selian Agricultural Research Institute. Project website: http://africa-rising.net